The Implementation of Multi Attribute Utility Theory Method for Employee Performance Appraisal in The Regional Office of the Ministry of Law and Human Rights (Kemenkumham) of Bengkulu Province - Neti, Kusma (Jurnal Komputer, Informasi dan Teknologi, 2021)
Employee performance appraisal aims to find employees with good performance qualities in accordance with the vision and mission of the Ministry of Law and Human Rights. The difficulty that occurs in conducting the employee performance appraisal process is the difficulty of selecting employees properly and fairly due to the diversity of educational backgrounds, experiences, competencies and portfolios in which it becomes a concern in determining outstanding employees. To overcome these obstacles, a decision support system for the MAUT method is needed to be used as an additional medium to support the decision-making process. The implementation of the system uses the Visual Basic 2010 programming language and the method used in this study is the Waterfall Method. From the results of the tests carried out, it can be concluded that employee performance appraisal by MAUT can be done well by ranking, where the highest value is 0.76 and the lowest value is 0.09 from the MAUT ranking process which can then be reported in the form of an employee performance report.